2013
DOI: 10.1089/fpd.2013.1504
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals in Lowbush Wild Blueberry InactivateEscherichia coliO157:H7 by Damaging Its Cell Membrane

Abstract: The antimicrobial activity and model of action of polyphenolic compounds extracted from lowbush wild blueberries (LWB) were studied against Escherichia coli O157:H7. Polyphenols in LWB were extracted using 80% vol/vol methanol and designated as total blueberry phenolics (TBP). The fraction was further separated by a C-18 Sep-Pak cartridge into monomeric phenolics acids (MPA) and anthocyanins plus proanthocyanidins (A&P). The A&P fraction was further separated into anthocyanins and proanthocyanidins using a LH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…A significant damage on cell membrane may be due to the loss of their physiological functions such as permeability barrier, membrane potential, and efflux pump activity. However, the present results directly indicate that that LED illumination altered the permeability of cell membranes since PI (red fluorescence) with high molecular weight can only enter into the cells with the loss of membrane function as a permeability barrier (Bleichert et al, 2014;Joux & Lebaron, 2000;Lacombe et al, 2013). A similar result of cytoplasmic membrane damage was observed in E. coli cells exposed to the oxidizing effects of copper alloy, UV light, and TiO 2 due to lipid peroxidation (Hong, Kang, Michels, & Gadura, 2012).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A significant damage on cell membrane may be due to the loss of their physiological functions such as permeability barrier, membrane potential, and efflux pump activity. However, the present results directly indicate that that LED illumination altered the permeability of cell membranes since PI (red fluorescence) with high molecular weight can only enter into the cells with the loss of membrane function as a permeability barrier (Bleichert et al, 2014;Joux & Lebaron, 2000;Lacombe et al, 2013). A similar result of cytoplasmic membrane damage was observed in E. coli cells exposed to the oxidizing effects of copper alloy, UV light, and TiO 2 due to lipid peroxidation (Hong, Kang, Michels, & Gadura, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…LIVE/DEAD ® BacLight™ is dual nucleic acid staining method used to evaluate cellular viability based on the changes in their membrane permeability. Green fluorochrome SYTO ® 9 (480/500 nm) of low molecular weight (~10 Da) is able to penetrate both intact and damaged cell membranes, whereas red fluorochrome PI (490/635 nm) of higher molecular weight (668 Da) can penetrate only damaged membranes, displacing SYTO ® 9 with red fluorescence (Bleichert, Santo, Hanczaruk, Meyer, & Grass, 2014;Joux & Lebaron, 2000;Lacombe, Tadepalli, Hwang, & Wu, 2013). In this study, nonilluminated cells showed green fluorescence of SYTO ® 9 stain, indicating that they maintained intact cell membrane over the exposure time (7.5 h) at 10 C. On the other hand, some LEDilluminated cells revealed red fluorescence, indicating that these cells underwent a loss in the physical membrane integrity due to exposure to 405 ± 5 nm LED treatment.…”
Section: Bacterial Sensitivity To Bile Salts and Nacl By 405 ± 5 Nm Lmentioning
confidence: 99%
“…The LIVE/DEAD staining of SYTO®9 and propidium iodide (PI) bound to nucleic acid is able to distinguish between damaged and intact bacterial membranes. Green fluorescing SYTO®9 (485/500 nm) penetrates the cytoplasmic membranes of both intact and damaged cells due to low molecular weight (~10 Da), while red fluorescing PI (490/635 nm) of higher molecular weight (668 Da) is only able to enter the damaged cytoplasmic membranes, resulting in a reduction in the intensity of SYTO®9 when two stains coexist within the cell [29][30][31]. In this study, healthy and non-illuminated cells exposed to 10°C for 7.5 h revealed green fluorescent signal of SYTO®9, whereas some LED-illuminated cells showed red fluorescence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, plant-derived alkaloids, terpenes and phenolics have antiparasitic and antimicrobial properties (19)(20)(21)(22) and sesquiterpene lactones have antiamoebic, antibacterial and antifungal actions (23)(24)(25) . Since the pioneering work of Niezen et al (26) in New Zealand with tannin-containing legumes, it is known that condensed tannins have anthelmintic properties, mainly through: (1) lower establishment of the infective third-stage larvae (L3) in the host, (2) lower excretion of eggs by adult worms and (3) impaired development of eggs into L3 (27) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%